Coordination Relationship Between Bhabinkamtibmas and Village Officials in Crime Cases of Theft through Penal Mediation - Agnessia Kurnia Puspa Herwoko (IHSA Institute, 2019)
The concept in the criminal justice system is not known as mediation, but at present there is a growing reasoning mediation which is examined at the level of regulation under the law which is partial and limited in nature, so that the mediation mediation is regulated in the Letter of the Chief of the National Police No. Pol: B / 3022 / XII / 2009 / SDEOPS on Handling Cases through Alternative Dispute Resolution (ADR). Communities that are exposed to the scope of the Pekon Rembuk regulation in the Marga Tiga still have the trust of those whose level is higher than the community and the values contained in the settlement of criminal cases committed through the mediation of the said criminal. The problems in this thesis are: 1. What is the model for solving theft cases through reasoning mediation by Bhabinkamtibmas and village apparatus in Margatiga village? 2. How is the coordination between Bhabinkamtibmas and the village apparatus in settling cases of theft through criminal mediation? The approach to the problem in this paper uses a normative juridical approach and empirical jurisdiction. The sources and types of data used are primary data and secondary data. The data of collectted by literature study and field studies. Data analysis used is qualitative analysis. Based on the results of the research and discussion, it was concluded that the problem solving was carried out by way of Pekon Rembuk. This settlement process was with a model of finding parties and village officials and police institutions or local village Bhabinkamtibmas with mekanisme: 1. Prepeace 2. Peace 3. Post peace. In the three processes that have been passed, this case of theft can indeed be resolved through reasoning mediation between the two parties with the mediator of the village apparatus and Bhabinkamtibmas. Because indeed problems like this can be done through village meetings or other languages in Rembuk Pekon which have often been carried out by village officials and other institutions that are indeed capable of law or understand how to solve cases or problems that exist within the village community in the Marga Tiga. The coordination relationship between Bhabinkamtibmas and the village apparatus in settling criminal cases through criminal mediation is based on the relationship between the village apparatus and members of the local village police namely Bhabinkamtibmas.